О происхождении столбовых гробниц Лесостепи скифского времени - Гречко, Д. С. (Давнина. Харківський історико-археологічний щорічник)
Резюме Гречко Д. С. Про походження стовпових гробниць Лісостепу скіфського часу Стаття присвячена вивченню традиції спорудження дерев’яних стовпових гробниць Північного Причорномор’я доби бронзи — початку раннього залізного віку. Робиться висновок про її конвергентну появу за доби пізнього бронзового віку у іраномовного населення Євразії. Її розвиток у перед- і ранньоскіфський час в Степу та Лісостепу Північного Причорномор’я відбувався у результаті взаємодії місцевих белозерських та східних (центральноказахстанських) елементів. На цей процес впливали культурні імпульси з Центральної Європи. Ключові слова: Північне Причорномор’я, доба бронзи — ранній залізний вік, стовпові гробниці, іраномовні кочовики. Summary D. Grechko. To the Question About Pillar Tombs of Forest-steppe of the scythian Times The article is dedicated to the investigation of the tradition associated with the building of wooden pillar tombs in the North Black Sea region of the Bronze Age — the beginning of the early Iron Age. The results indicated that this tradition resembles the one that appeared among Iranian-speaking population in the late Bronze Age. The development of the tradition on the territory of the steppe and forest-steppe of the North Black Sea region in the pre- and early Scythian times resulted from the interaction of the local Belozersky and eastern (peculiar for central Kazakhstan) elements. The cultural impulses from Central Europe had a particular impact on this process. Key words: the North Black Sea region, the Bronze Age — the early Iron Age, pillar tombs, the Iranian-speaking nomads.